Comparison of serum vitamin D levels between healthy and ADHD children - Armon Massoodi; Sakineh Javadian Koutanaei; Zahra Faraz; Zahra Geraili; Seyedeh Maryam Zavarmousavi (Caspian Journal of Internal Medicine, 2023)
Background: The most common psychiatric disorder in childhood is Attention-deficit/hyperactivity disorder (ADHD). Researchers have studied the effects of micronutrients on ADHD in recent years, but vit D deficiency has received less attention. In this study, serum vit D levels were compared between healthy and ADHD children. Methods: This case-control study was carried out, in 2020, on 6-to-12-years-old children. There were 45 children with ADHD in the case group and 45 healthy children in the control group. Intravenous blood samples were taken from each child to measure serum vitamin D levels. A p-value < 0.05 was considered as significant. Results: Mean serum vit D levels in children with ADHD (17.34±8.37 ng / ml) were significantly lower than those in the control group (23.02±10.97 ng / ml) (P= 0.007). There were no significant differences in mean serum levels of vit D due to ADHD subtypes. Mean serum vit D levels were not significantly associated with the gender of children with ADHD. There was an inverse correlation between vit D levels and the severity of ADHD, but it was not statistically significant. Conclusion: The present study showed that children with ADHD had significantly lower serum vit D levels than healthy controls.